Sunday

August 2, 2015

August 2, 2015

Posted by **pkd** on Wednesday, January 5, 2011 at 5:20pm.

- Math !!!!ASAP!!!!! -
**Kay**, Wednesday, January 5, 2011 at 5:31pmx+(x-31)+(x-22)= 61

Expand this expression first

ie. x+ x -31 + x - 22 = 61

ie. 3x -31 -22 = 61

3x - 53 = 61

3x = 61 + 53

3x = 114

x = 114/ 3

x = 38

Done!

- Math !!!!ASAP!!!!! -
**lissa**, Wednesday, January 5, 2011 at 5:31pmyou combine all common factors so 3x-53=61. then add 53 to both sides to get 3x=114. then divide both sides by 3 to get x=38 :)